KONVERGENSI HARGA PANGAN POKOK ANTAR WILAYAH DI INDONESIA - Emilia Khristina Kiha; Wiwiek Rindayati (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2013)
In Indonesia, the increase in food prices usually results in the rise in the inflation rate. To cope with this problem, a better food distribution among regionsis absolutely required. This study aimed to describe the dynamics of food prices, to test the convergence level of food prices and to analyze the factors that influence the changes in food prices between regions in Indonesia. The data used were obtained from the Central Agency of Statistics and the Ministry of Agriculture from  2002 to 2010. The method used was analysis of dynamic panel data (First Difference-Generalized Methode Moment/FDGMM). The results of the study showed that all commodities of food prices were convergent, sugar at the highest level and rice at the lowest, while the factors that influence changes in food prices were production rate, Gross Domestic Product (GDP) and population.  Keywords: Convergence, Food Prices, GMM Panel Data